ANALISIS MOTIVASI KERJA GURU DALAM PENYUSUNAN PERANGKAT PEMBELAJARAN DI SDN PONDOK KACANG TIMUR 01 KOTA TANGERANG SELATAN - Candra Puspita Rini; Saktian Dwi Hartantri (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to find out how the motivation of teachers in the preparation of learning devices, the application of learning devices, and how to use media in the learning process. This study uses descriptive qualitative methods by collecting data in the form of observations, interviews, questionnaires, and documentation. And with the technique of checking the validity of the data using triangulation. The teacher has an important role in classroom learning. Therefore, to carry out quality learning, one of the tasks of the teacher is to develop learning tools optimally. And based on the results of the study, it can be seen that the work motivation of teachers in the preparation of learning devices is considered to be quite high. This is evidenced by the results of several studies and discussions, where the teacher was very trying to get the best results. Starting from attending training or workshops to improve teacher competency, school principal regulations that require teachers to develop learning tools, and the most important is teacher awareness of their obligations and responsibilities in the preparation of learning devices. The application of learning tools in the classroom is also considered to be quite high. This is evidenced by the results of the questionnaire 81.2% of teachers like to implement learning tools. However, the use of media in learning is still considered low. Because there are only 2 teachers who use the media. And the lack of facilities provided by schools for the use of learning media.